A family of doped lanthanide metal–organic frameworks for wide-range temperature sensing and tunable white light emission. Issue 8 (6th February 2017) - Yang, Yan; Chen, Lian; Jiang, Feilong; Yu, Muxin; Wan, Xiuyan; Zhang, Bo; Hong, Maochun
Abstract : A series of binary and ternary mixed LnMOFs with high stability showing potential applications in wide-range thermosensors and white LEDs are reported. Abstract : A family of lanthanide MOFs (LnL) with high thermal and air stability have been successfully synthesized. Based on this robust framework, a series of binary and ternary co-doped LnMOFs, Eu x Tb y L ( y = 1− x ) andEu x Tb y Gd1− x − y L, are achieved for use as ratiometric temperature sensors and white-light-emitting materials. In a binary co-doped system, Eu0.0066 Tb0.9934 L andEu0.0089 Tb0.9911 L show good linear responses to temperature with high sensitivities over a very wide range (from 77 K to 450 K), of whichEu0.0066 Tb0.9934 L exhibits a maximum relative sensitivity ( S m ) of 3.76% K −1 at 450 K. This value is comparable to those of other excellent LnMOF thermometers reported recently whereas the response temperature range is greatly enlarged. The ternary mixed LnMOFs based on energy transfer of different lanthanide ions as ratiometric luminescent thermometers are firstly investigated, in whichEu0.013 Tb0.060 Gd0.927 L displays an extremely high sensitivity ( S m = 6.11% K −1 ), representing one of the largest values reported so far in mixed LnMOFs. Furthermore, by virtue of carefully adjusting the composition of the mixed LnMOFs and the wavelength of excitation, the emission color can be systematically modulated and a tunable white light emission material, Eu0.0062 Tb0.0087 Gd0.9851 L, is successfully developed.